A STUDY ON STRESS LEVEL AND COPING STRATEGIC AMONG PRIMARY TAMIL SCHOOL TEACHERS - Gugeneswari, Karunanithi; Kumaran, Suberamanian (PEOPLE: International Journal of Social Sciences, 2015)
The purpose of this cross sectional study is determine the level of stress and coping strategies among primary school Tamil teachers in Selangor state with regards to location and to investigate the relationship between the stress level and coping .Approximately 240 teachers became the research respondents. The data was gained by employing DASS 21 and Ways of Coping Questionnaire. Data was analyzed using MINITAB 14. Statistical analysis for the first and second objective is done based on ANOVA. Analysis shows that even though rural and urban teachers’ depression level is the same, urban teachers’ have higher anxiety and stress level. Besides, rural teachers use planful problem solving as their way of coping with stress whereas urban teachers use accepting responsibilities as the highest way of coping with stress. Through the analysis for stress level and location, since the p value is less than 0.05, null hypotheses can be rejected and it proves that there is a significance difference between the stress level and location of the school. As for the analysis on coping and location, since the p value is less than 0.05, the null hypotheses can be rejected and it proves that there is a significant difference between coping strategies utilized by urban and rural teachers. Analysis to find if there is relationship between stress level and coping is done using One Way MANOVA analysis. Since all the p values are less than 0.05, the null hypotheses can be rejected and there is a significant difference between stress levels and coping level. It is intended that the results of this study will help to create awareness for Tamil school teachers to reach and maintain effective stress coping strategies for optimal level of emotional wellbeing